Bone Flare to Androgen Deprivation Therapy in Metastatic, Hormone-Sensitive Prostate Cancer on 68Ga-Prostate-Specific Membrane Antigen PET/CT. (November 2018) - Zacho, Helle D.; Petersen, Lars J.
Abstract : Abstract: A 69-year-old man with newly diagnosed prostate cancer PSA 274 ng/mL, Gleason 4+3, T-stage 3b) underwent 68 Ga-PSMA PET/CT for staging with follow-up scans 6 and 13 weeks after androgen deprivation therapy (ADT) initiation. Six weeks after ADT initiation, lymph node metastases observed at staging showed metabolic and radiological regression, whereas the skeleton showed increased PSMA uptake in existing bone metastases and several new PSMA-avid lesions. Skeletal PSMA uptake decreased after 13 weeks of ADT, and prostate-specific antigen decreased to 16 ng/mL. These findings suggest the presence of the flare phenomenon to ADT in bone metastases seen on PSMA PET/CT.